Right Here, Right Now: User Perceptions of In-Place Contextual Privacy Options - Dehling, Florian; Tolsdorf, Jan; Lo Iacono, Luigi; Justus Liebig University Giessen (My University, 2025)
In modern online services and apps, legally required privacy information and controls are often placed on separate pages or menus, forcing users to leave their primary tasks to review privacy statements or adjust settings. This disrupts usability by causing unnecessary friction, context switching, and information overload. We propose In-Place Contextual Privacy Options (IPCPOs), a Transparency-Enhancing Technology (TET) that integrates relevant privacy controls directly into a user’s workflow. IPCPOs tailor privacy information and settings to the immediate context, reducing the set of controls and information provided to contextual needs. In a study with 442 participants in an e-commerce setting, we found that IPCPOs should prioritize information on personal data types, processing purposes, and data recipients, alongside offering privacy controls. While IPCPOs score high on perceived transparency, only perceived control and privacy concerns significantly drive adoption intention. This work demonstrates how IPCPOs help comply with data protection obligations while reducing usability burdens.
Keywords: transparency-enhancing technology; tet; contextual transparency; contextual privacy control; sem; ddc:004